2005
DOI: 10.1590/s1806-83242005000300009
|View full text |Cite
|
Sign up to set email alerts
|

Response of osteoblastic cells to titanium submitted to three different surface treatments

Abstract: In the complex process of bone formation at the implant-tissue interface, surface properties are relevant factors modulating osteoblastic function. In this study, commercially pure titanium (cp Ti) samples were prepared with different surface characteristics using chemical attack with a sulfuric acid/hydrochloric acid based solution (treatment A); chemical attack plus anodic oxidation using phosphoric acid (treatment B); and chemical attack plus thermal oxidation followed by immersion in a sodium fluoride solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…In contrast, the fluoride concentration detected in the implant surfaces showed a positive correlation to the pull‐out results, confirming a positive net effect on bone retention. This effect has also been observed in earlier studies 19, 38, 47. Although the fluoride amount in the surfaces of the groups treated with HF at 0.001 and 0.01 vol % were equal, the implant performance differed during the pull‐out tests; thus, fluoride was obviously not the only element of the surface modification that affected the implant performance in vivo .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, the fluoride concentration detected in the implant surfaces showed a positive correlation to the pull‐out results, confirming a positive net effect on bone retention. This effect has also been observed in earlier studies 19, 38, 47. Although the fluoride amount in the surfaces of the groups treated with HF at 0.001 and 0.01 vol % were equal, the implant performance differed during the pull‐out tests; thus, fluoride was obviously not the only element of the surface modification that affected the implant performance in vivo .…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, implants with rough surfaces are typically associated with higher retention force in bone, when compared with smooth‐surface implants 33–36. However, too rough surfaces have shown lower bone attachment strength than less rough surfaces 37, 38. The analysis was not aimed to show that rough surfaces are better than smooth, but to understand which parameters of the surface topography influence most the implant retention in bone.…”
Section: Discussionmentioning
confidence: 99%
“…Another important feature is the surface free energy, which influences cellular adhesion strength and proliferation. It has been shown that low cell adhesion strength is related to the dispersive component of SFE [21]. Previous works also demonstrated that: the more hydrophilic the material the more cells will adhere on the surface [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…*Corresponding author: cimenogluh@itu.edu.tr ©KIM and Springer Besides wear resistance, biological response is another issue to be taken into consideration because it has a crucial importance on long term bone/implant interface stability and functional performance of the implants. To the knowledge of the authors, there are a limited number of reports focusing on the biological response of titanium-based materials after the TO process [18][19][20][21][22][23]. Therefore, this study aims at contributing to the existent knowledge by analyzing the in-vitro performance of original and thermally oxidized Ti6Al7Nb alloy by means of wear and biological tests.…”
Section: Introductionmentioning
confidence: 99%